ChemInform Abstract: Iron‐Catalyzed Regioselective Alkoxycarbonylation of Imidazoheterocycles with Carbazates. Issue 31 (14th July 2016) - Gao, Yongyuan; Lu, Weiye; Liu, Ping; Sun, Peipei
Abstract: This is presented in continuation of studies on selective direct C—H functionalization of electron‐rich aryl rings or heterocyclic compounds.